General surface grafting strategy-derived carbon-modified graphitic carbon nitride with largely enhanced visible light photocatalytic H2 evolution coupled with benzyl alcohol oxidation. Issue 11 (24th February 2021) - Wang, Haifei; Zhang, Jihua; Jin, Xu; Wang, Xiaoqi; Zhang, Fu; Xue, Jierui; Li, Yapeng; Li, Jianming; Zhang, Genqiang
Abstract : A general surface grafting strategy followed by in situ carbonization was developed to prepare the carbon-modified g-C3 N4 with robustly enhanced visible light photocatalytic activity for H2 evolution coupled with benzyl alcohol oxidation. Abstract : Carbon-modified g-C3 N4 manifests increasing prospects in the photocatalytic realm. However, there are some challenges, such as difficult large-scale preparation, weak interface connection, limited active sites, and inefficient light utilization, which restrain the further utilization for carbon modified g-C3 N4 . To solve these disadvantages, we recommended a novel and general surface grafting strategy followed by the in situ carbonization treatment to obtain carbon-modified graphitic carbon nitride (CMCN). Experimental results disclose that the introduced carbon connected intimately with g-C3 N4 by edge N atoms, which dramatically improve the charge transfer kinetics. CMCN presents incredibly reinforced visible light photocatalytic activity with an impressive hydrogen evolution rate of 5.549 mmol g −1 h −1, which is about 13.3 times higher than that of pure g-C3 N4 . Theoretical calculation results show that the introduced carbon can form a new intermediate state between the bandgap, which could capture the photoexcited electrons and reinforce the visible light absorption. Importantly, the practicality of the CMCN material is further demonstrated by replacing a sacrificial reagent with benzyl alcohol conversion to produce value-added benzaldehyde, where the decent evolution rates of 0.288 and 0.230 mmol g −1 h −1 can be achieved for H2 and benzaldehyde, respectively.